Mucocutaneous manifestations of dengue fever - Thomas Emy; John Mary; Kanish Bimal (Wolters Kluwer Medknow Publications, 2010)
Dengue viral infection is a cause of considerable morbidity and mortality and may be associated with a variety of mucocutaneous manifestations that may provide important early clues to the diagnosis of this condition. Cutaneous and mucosal findings like confluent erythema, morbilliform eruptions, and hemorrhagic lesions may figure prominently in the clinical features of dengue. The differential diagnoses include a large number of bacterial and viral exanthems as well as drug rash.